Method for manufacturing exfoliated MAX using supercritical carbon dioxide
Patent Information
- Application Number
- KR1020230057137
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-05-02
- Publication Date
- 2026-09-02
- Estimated Expiration
- 2043-05-02
Smart Images

Figure 112023048972414-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention belongs to the field of manufacturing technology for MXenes, and in particular to M physically exfoliated by supercritical CO2. n+1 AX n This is about a method for manufacturing sheets. Background Technology
[0002] MXenes, which are two-dimensional layered transition metal carbide and nitride materials, possess unique physical, chemical, and mechanical properties such as high specific surface area, structural flexibility, diversity of surface tuning chemistry, high conductivity, and abundant surface d-orbital electrons, and are receiving widespread interest in fields such as energy storage and power generation, electromagnetic shielding, gas and pressure sensors, photocatalysts, and electrocatalysts.
[0003] MXenes can be obtained by exfoliating MAX, which imparts clay-like properties, and most methods for manufacturing MXenes utilize chemical exfoliation such as HCl + LiF or HF etching. MXenes obtained through chemical exfoliation exhibit low oxidation stability, resulting in a decrease in electrical conductivity within a few days. Furthermore, the high corrosiveness, toxicity, operational hazards, and environmental impact of HF are significant issues that cannot be ignored. Therefore, there is a need to explore and develop new etching methods that replace the HF etching process with milder, less toxic, and environmentally friendly alternatives. Prior art literature
[0004] Republic of Korea Published Patent No. 2021-0015689 International Published Patent No. 2021 / 076639 The problem to be solved
[0005] In order to solve the above problems, the present invention aims to provide an eco-friendly physical exfoliation method that can exhibit high electrical conductivity even after a long period compared to oxidized MXene without changing the chemical composition of MAX through a supercritical carbon dioxide process. means of solving the problem
[0006] The method for manufacturing exfoliated MAX according to the present invention comprises a first step of preparing a MAX dispersion solution by dispersing a MAX precursor in an organic solvent, a second step of drying under supercritical carbon dioxide, and a third step of rapidly expanding under supercritical carbon dioxide.
[0007] The MAX precursor is characterized by being represented by the following chemical formula 1.
[0008] [Chemical Formula 1]
[0009] M n+1 AX n
[0010] (In the above Chemical Formula 1, M is a transition metal, A is a Group 13 or Group 14 element, X is carbon (C) or nitrogen (N), and n is 1 to 4)
[0011] The above transition metal comprises one or more selected from the group consisting of scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), zirconium (Zr), niobium (Nb), molybdenum (Mo), hafnium (Hf), tantalum (Ta), and tungsten (W), and A comprises one or more selected from the group consisting of aluminum (Al), silicon (Si), gallium (Ga), germanium (Ge), indium (In), tin (Sn), thallium (Tl), and lead (Pb).
[0012] The particle size of the MAX precursor is characterized by being 75㎛ or less.
[0013] The organic solvent is an alcohol-based solvent and may be one or more selected from methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, methoxymethanol, ethoxymethanol, methoxypropanol, ethoxypropanol, and diacetone alcohol.
[0014] The concentration of the MAX precursor in the MAX dispersion solution should be 4 mg / ml to 6 mg / ml.
[0015] The reaction temperature of the second stage is 40°C to 50°C, the reaction pressure is 80 bar to 100 bar, and the reaction time is 1.5 to 2.5 hours.
[0016] The reaction temperature of the third step is 80°C to 120°C, the reaction pressure is 80 bar to 120 bar, and the reaction time is 0.5 to 1.5 hours.
[0017] The present invention also includes MAX exfoliated by supercritical carbon dioxide treatment, manufactured by this method.
[0018] The MAX peeled off according to the present invention has a value of 0.5 at% or more for △C (at%) defined by the following formula.
[0019] △C (at%) = C0 - C1
[0020] Here, C0 is the Ti-Al atomic content (at%) of the MAX precursor measured by X-ray photoelectron spectroscopy (XPS), and C1 is the Ti-Al atomic content (at%) of the MAX layer measured by XPS after the supercritical carbon dioxide exfoliation process.
[0021] The MAX exfoliated according to the present invention is characterized by having a peak at a diffraction angle 2θ=52.0°±1.0° in the XRD spectrum, and not having peaks at diffraction angles 2θ=9.5°±1.0°, 2θ=19.0°±1.0°, and 2θ=38.5°±1.0°.
[0022] The electrical conductivity of MAX exfoliated according to the present invention is 250 S / cm or more at a pressure of 10 MPa. Effects of the invention
[0023] The method for manufacturing exfoliated MAX using supercritical carbon dioxide according to the present invention does not use hydrofluoric acid, making it safe for workers and the environment, and allows for quick and easy manufacturing. Furthermore, it can maintain electrical conductivity for a long period, thereby improving stability and productivity as an energy storage material. Brief explanation of the drawing
[0024] Figure 1 is a schematic diagram of a stripping process using supercritical carbon dioxide. Figure 2 is a diagram showing the supercritical fluid region in the carbon dioxide phase diagram. Figure 3 is a figure comparing the physical peeling process (left) and the chemical peeling process (right). Figure 4 shows the results observed with a scanning electron microscope (SEM). Figure 5 shows the results of X-ray diffraction analysis (XRD). Figure 6 shows the results of X-ray diffraction analysis (XRD). Figure 7 shows the results of analysis using X-ray photoelectron spectroscopy (XPS). Figure 8 shows the results of analysis using X-ray photoelectron spectroscopy (XPS). Figure 9 shows the results of measuring electrical conductivity using a powder resistance meter. Specific details for implementing the invention
[0025] Hereinafter, a method for manufacturing exfoliated MAX using supercritical carbon dioxide will be described in detail with reference to the drawings.
[0026] Terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.
[0027] Therefore, the embodiments described in this specification and the configurations described in the drawings are merely the most preferred embodiments of the present invention and do not represent all of the technical ideas of the present invention; thus, it should be understood that various equivalents and modifications that can replace them may exist at the time of filing this application.
[0029] In an exemplary embodiment of the present invention, a method for producing exfoliated MAX is provided, comprising a first step of preparing a MAX dispersion solution by dispersing a MAX precursor in an organic solvent, a second step of drying under supercritical carbon dioxide, and a third step of rapidly expanding under supercritical carbon dioxide.
[0030] Figure 1 shows a schematic diagram of the exfoliation process using supercritical carbon dioxide. Since supercritical CO2 has no surface tension, it can easily penetrate porous structures, and because of its fast diffusion rate, it can penetrate the layers and expand the MAX sheet as shown in Figure 1.
[0031] In the present invention, the step of preparing a MAX dispersion solution by dispersing a MAX precursor in an organic solvent is performed first. The MAX precursor is characterized by being represented by the following chemical formula 1.
[0032] [Chemical Formula 1]
[0033] M n+1 AX n
[0034] (In the above Chemical Formula 1, M is a transition metal, A is a Group 13 or Group 14 element, X is carbon (C) or nitrogen (N), and n is 1 to 4)
[0035] The above transition metal comprises one or more selected from the group consisting of scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), zirconium (Zr), niobium (Nb), molybdenum (Mo), hafnium (Hf), tantalum (Ta), and tungsten (W), and A comprises one or more selected from the group consisting of aluminum (Al), silicon (Si), gallium (Ga), germanium (Ge), indium (In), tin (Sn), thallium (Tl), and lead (Pb).
[0036] The MAX precursor is a crystal composed of stacked unit layers of 10 or more layers, in which the transition metal layer (M layer) and the carbon layer or nitrogen layer (X layer) are strongly bonded to each other by an aluminum layer or silicon layer (A layer). Therefore, to increase the reaction rate, MAX is formed into uniform sizes and then immersed in a sufficient amount of organic solvent.
[0037] MAX in pellet form is finely ground into a powder using a mortar and pestle, and then sieved using a mesh of 200 to 400 so that the particle size is 75 μm or less. The MAX obtained in this way is dispersed in an organic solvent at a concentration of 4 mg / ml to 6 mg / ml. The organic solvent is an alcohol-based solvent, and one or more selected from methanol, ethanol, n-propanol, isopropanol, n-butanol, 2-butanol, isobutanol, methoxymethanol, ethoxymethanol, methoxypropanol, ethoxypropanol, and diacetone alcohol may be used, and among these, it is most preferable to use ethanol.
[0038] In order to ensure that the MAX powder is well dispersed, a process of ultrasonically crushing it using a sonication bath or tip is performed. The MAX dispersion solution, which is sufficiently dispersed in this way, is filled into a supercritical equipment chamber and subjected to drying and rapid expansion processes. Since supercritical carbon dioxide is formed only at a critical temperature of 31.1°C or higher and a critical pressure of 7.4 MPa (74 bar) or higher (Fig. 2), temperature and pressure are important factors in the supercritical reaction.
[0039] The second stage supercritical carbon dioxide drying process is carried out by reacting for about 1.5 to 2.5 hours at a temperature of 40°C to 50°C and a pressure of 80 bar to 100 bar (8 MPa to 10 MPa). Most preferably, drying is performed for 2 hours at 45°C and 100 bar.
[0040] The third stage supercritical carbon dioxide rapid expansion process is carried out for about 0.5 to 1.5 hours at a temperature of 80°C to 120°C and a pressure of 80 bar to 120 bar (8 MPa to 12 MPa). Most preferably, the reaction is carried out for 1 hour at 100°C and 120 bar. Once the reaction is complete, the MAX sample is retrieved.
[0041] Hereinafter, comparative examples and embodiments will be described in detail to specifically explain the present invention. However, embodiments according to the present invention may be modified in various different forms, and the scope of the present invention should not be interpreted as being limited to the embodiments described below. The embodiments of the present invention are provided to more completely explain the present invention to those with average knowledge in the art.
[0043] Examples and Comparative Examples
[0044] An unexfoliated MAX precursor was designated as Comparative Example 1, a chemical exfoliation process using a fluorine compound as Comparative Example 2, and a physical exfoliation process using supercritical carbon dioxide as Examples 1 to 5. The two reactions are briefly schematically illustrated in FIG. 3. The supercritical fluid process consists of two consecutive steps under different CO2 conditions: supercritical drying (SD) and rapid expansion of the supercritical suspension (RESS). The MXene chemically exfoliated by etching with HF is Ti3C2T, which is split into thin flakes by etching Ti3AlC2 with HF or HCl and LiF. x It was used to obtain. This method causes a decrease in electrical conductivity because it is easily oxidized to TiO2 by functional groups such as -OH / -F at the separated interface.
[0046] (Comparative Example 2) Ti exfoliated by chemical method 3 AlC 2
[0047] Ti3AlC2MXene was prepared by adding a mixture of HCl and LiF to Ti3AlC2MAX. For the MXene synthesis solution, 10 mL of distilled water and 10 mL of hydrochloric acid were added and stirred at 550 rpm, after which 2 g of LiF was slowly added. 2 g of Ti3AlC2 powder was sieved through a 200 mesh and added to the Ti3AlC2 synthesis solution. The MXene synthesis solution was maintained at room temperature (21°C) for 24 hours and then stirred at 550 rpm. After 24 hours, when the synthesis reaction was complete, excess distilled water was added to the MXene synthesis solution, and the solution was centrifuged and rinsed to adjust the pH to 6-7. The MXene precipitated after centrifugation was exfoliated by adding 40 mL of distilled water and shaking for 80 minutes. Centrifugation was performed again at 3000 rpm to obtain the exfoliated MXene dispersed in the supernatant. This oxidized MXene was left in distilled water for two weeks and then freeze-dried to obtain a powder.
[0049] (Examples 1-5) Ti exfoliated with supercritical carbon dioxide 3 AlC 2
[0050] Exfoliated MAX (supercritical CO2-MAX) can be obtained by treating MAX with supercritical CO2 fluid. MAX (Ti3AlC2) powder was purchased from Y-Carbon, Ltd. in Ukraine. The Ti3AlC2 powder (85–95 wt% Ti3AlC2, 5–10 wt% TiC, 1–5 wt% Al2O3) was sieved sequentially using 200 and 400 mesh. 200 mg of Ti3AlC2 was added to 40 mL of ethanol to prepare a solution with a concentration of 5 mg / mL. The solution was subjected to sonication in a sonication bath for 1 hour, tip sonication at 40% amplitude for 1 minute, and further sonication in a sonication bath for 1 hour.
[0051] The solvent was removed from the primary dispersed MAX solution using a freeze-drying or supercritical drying process to obtain MAX powder. In the supercritical drying process, the dispersed MAX solution was dried and exfoliated using supercritical CO2 (ILSHIN AUTOCLAVE, SCD-BP-1, Korea). For the supercritical drying process, an ultrasonically treated MAX dispersion (1.6 g, 5 mg / mL) was placed in a supercritical carbon dioxide chamber and dried for 2 hours at a temperature of 45°C and a CO2 pressure of 100 bar. During this process, the outlet valve was opened to allow CO2 gas to flow and remove ethanol, thereby obtaining MAX aerogel powder.
[0052] The freeze-dried MAX powder was introduced into a supercritical chamber to carry out a rapid expansion process, and the supercritical dried MAX powder was subsequently carried out in a single step rapid expansion process. The rapid expansion process was carried out for 1 hour under two conditions: (1) a temperature of 36°C and a CO2 pressure of 82 bar, and (2) a temperature of 100°C and a CO2 pressure of 120 bar.
[0053] The manufacturing methods of the comparative examples and examples are shown in Table 1 below.
[0054] Drying process Rapid expansion process Comparative Example 1 doesn't exist doesn't exist Example 1 doesn't exist 100℃, 120bar, 1 hour Example 2 Freeze-drying Example 3 Supercritical drying (45℃, 100 bar, 2 hours) Example 4 Freeze-drying 36℃, 82 bar, 1 hour Example 5 Supercritical drying (45℃, 100 bar, 2 hours)
[0056] (Experimental Example 1) Exfoliated Ti 3 AlC 2 Analysis of external characteristics
[0057] The exfoliated MAX structure was analyzed using a field emission scanning electron microscope (FE-SEM) (CLARA, TESCAN, Czech Republic). Figure 4 shows scanning electron microscope (SEM) images of Comparative Example 1, Example 5, Example 3, and Comparative Example 2. Comparative Example 1(a) shows that the natural MAX has a multilayer stacked structure. However, as in Example 5(b), when drying and rapid expansion were performed at 36°C, it was confirmed that the layered structure of the MAX expanded. In contrast, the MAX sheet of Example 3(c), which was dried and rapidly expanded at 100°C, was exfoliated without a multilayer or stacked structure. The SEM image of Comparative Example 2(d) showed a sheet size similar to that of Example 3(c), indicating that MAX can be exfoliated through a supercritical CO2 process, just as it is possible with chemical etching.
[0059] (Experimental Example 2) Exfoliated Ti 3 AlC 2 Structural characteristics analysis
[0060] The powder XRD pattern of the exfoliated Ti3AlC2 was obtained using an X-ray diffractometer (SmartLab, Rigaku Corporation, Japan), and the XRD diffraction peaks were obtained in the 2θ range of 5-80°. The results are shown in Figures 5 and 6. The top black line represents the XRD peak of Comparative Example 1, which was not treated. Example 1 (red line) is the result of rapid expansion at 100°C and 120 bar without a drying process. Example 2 (green line) and Example 4 (magenta line) are the results of additional rapid expansion processes at 100°C / 120 bar and 36°C / 82 bar, respectively, after freeze-drying. Finally, Example 3 (blue line) and Example 5 (yellow line) were prepared by treating a MAX suspension of ethanol with a bath and tip sonication, then drying it with supercritical CO2 (45°C / 100 bar) and rapidly expanding it (100°C / 120 bar and 36°C / 82 bar), respectively.
[0061] The XRD peaks of Comparative Example 1 appeared at 2θ = 9.5°, 19.1°, 34.0°, 36.7°, 38.8°, 41.7°, 48.4°, 52.3°, 56.4°, 60.2°, 65.5°, 70.4°, 73.9°, and 74.1°, corresponding respectively to the peaks of (002), (004), (101), (103), {(008), (104)}, (105), (107), (108), (109), (110), (1011), (1012), (118), and (204) of the Ti3AlC2MAX crystal. FIG. 5(a) shows that the intensity of the (002) peak is the same for all except Example 3. Examples 4 and 5 have the same rapid expansion conditions and differ only in the drying method. Since Example 4 showed no difference compared to the XRD peak of Comparative Example 1, it can be seen that the conditions were unfavorable for MAX expansion. In contrast, the (108) peak was relatively prominent in Example 5. This indicates that the (002) peak was weakened due to the drying process effective for MAX expansion.
[0062] The (002), (004), and (008) peaks of Example 3 disappeared from the XRD pattern shown in Fig. 5(b). This means that both a drying process and a rapid expansion process are required to achieve MAX layer delamination. In the case of the rapid expansion process, the conditions of 100°C and 120 bar were more effective than the conditions of 36°C and 82 bar. This layer separation occurs because the bonding strength of aluminum with titanium is weak. In particular, Example 3 still shows the (108) peak in the XRD data corresponding to the crystal planes inside the layer, which means that the crystal structure inside the layer is not affected by the drying process and the rapid expansion process.
[0064] (Experimental Example 3) Exfoliated Ti 3 AlC 2 Analysis of physical properties
[0065] Whether the surface chemical structure was altered by supercritical CO2 treatment was measured using an X-ray photoelectron spectrometer (K-Alpha, Thermo Scientific, USA). Ti3AlC2 has major peaks for Al, C, Ti, and O with binding energies of approximately 74, 284, 458, and 532 eV, respectively. Fig. 7 shows the binding energies of Comparative Example 1 (ab) and Example 3 (cd). Fig. 8 shows the XPS spectra of C 1s and Al 2p of Comparative Example 1 and Example 3. In the XPS spectra of Ti 2p and O 1s, Ti-Al(Ti 2p 3 / 2 , 453.6 eV), Ti-C(Ti 2p 3 / 2 , 454.3 eV), Ti-O (455.6, 458.5, 464.2 eV), Ti-Al (Ti 2p 1 / 2 , 460.2 EV), Ti-C(Ti 2p 1 / 2 Peaks for Al-O (460.5), Al-Ti (530.4 eV), and Al2O3 (532.5 eV) appeared. Comparing Comparative Example 1 and Example 3, no significant difference was observed between the XPS spectra because supercritical CO2 treatment is a physical exfoliation method. In previous studies on MXene, the Ti-Al peak disappeared because Al was etched through LiF+HCl treatment. Furthermore, when a chemical etching method was used, aluminum was etched and replaced with OH, F, O, etc. The results of Example 3 in Fig. 8 (d) indicate that Al-O, Al-Ti-O, and Al-Ti peaks remain even after supercritical CO2 treatment. In other words, supercritical CO2 treatment did not affect the chemical composition of MAX.
[0067] (Experimental Example 4) Exfoliated Ti 3 AlC 2 Electrochemical characterization of
[0068] A powder sample of Example 3, physically exfoliated, was prepared and compared with the conductivity of Comparative Examples 1 and 2 by measuring the powder resistance as a function of pressure (Fig. 9). The electrical resistance of Comparative Example 1, Example 3, and Comparative Example 2 was measured using a powder resistance meter (HPRM-FA2; HANTCH, Korea). The measurement samples were prepared inside a cylindrical mold with a diameter of 25 mm and a height of 50 mm so that an equal amount of sample was sufficiently filled into the bottom surface. Comparative Example 1, Example 3, and Comparative Example 2 exhibited electrical conductivity values of 457, 303, and 46 S / cm, respectively, at a pressure of 10 MPa. Example 3 shows an increase in electrical conductivity with pressure. The electrical conductivity increased sharply at 6 MPa and 9 MPa, which is because the particles came into contact with each other to form a network. However, as can be seen in the SEM image of Fig. 9, Comparative Example 2 has lower electrical conductivity than Comparative Example 1 and Example 3 due to the presence of TiO2. Therefore, the combination of supercritical CO2 drying and rapid expansion is an effective method for maximum expansion and exfoliation without changing the chemical structure.
Claims
Claim 1 A method for manufacturing exfoliated MAX, comprising: a first step of preparing a MAX dispersion solution by dispersing a MAX precursor in an organic solvent; and a second step of drying under supercritical carbon dioxide. A method for manufacturing exfoliated MAX, comprising a third step of rapid expansion under supercritical carbon dioxide; wherein the second step is characterized by drying at 40 to 50°C for 1.5 to 2.5 hours at a pressure of 80 to 100 bar, and the third step is characterized by being performed for 0.5 to 1.5 hours under conditions of a temperature of 80°C to 120°C and a pressure of 80 to 120 bar, and wherein the exfoliated MAX has a peak at a diffraction angle 2θ=52.0°±1.0° as a result of XRD (X-ray Diffraction) spectrum measurement, and does not have peaks at diffraction angles 2θ=9.5°±1.0°, 2θ=19.0°±1.0°, and 2θ=38.5°±1.0°. Claim 2 A method for manufacturing exfoliated MAX according to claim 1, characterized in that the MAX precursor is represented by the following Chemical Formula 1 [Chemical Formula 1] M n+1 AX n (In the above Chemical Formula 1, M is a transition metal, A is a Group 13 or Group 14 element, X is carbon (C) or nitrogen (N), and n is 1 to 4) Claim 3 A method for manufacturing exfoliated MAX according to claim 2, characterized in that the transition metal comprises one or more selected from the group consisting of scantium (Sc), titanium (Ti), vanadium (V), chromium (Cr), zirconium (Zr), niobium (Nb), molybdenum (Mo), hafnium (Hf), tantalum (Ta), and tungsten (W). Claim 4 A method for manufacturing exfoliated MAX according to claim 2, wherein A comprises one or more selected from the group consisting of aluminum (Al), silicon (Si), gallium (Ga), germanium (Ge), indium (In), tin (Sn), thallium (Tl), and lead (Pb). Claim 5 A method for manufacturing exfoliated MAX according to claim 1, characterized in that the particle size of the MAX precursor is 75㎛ or less. Claim 6 A method for manufacturing exfoliated MAX according to claim 1, characterized in that the organic solvent is an alcohol-based solvent. Claim 7 A method for manufacturing exfoliated MAX according to claim 6, characterized in that the alcohol-based solvent is one or more selected from methanol, ethanol, n-propanol, isopropanol, n-butanol, 2-butanol, isobutanol, methoxymethanol, ethoxymethanol, methoxypropanol, ethoxypropanol, and diacetone alcohol. Claim 8 A method for preparing exfoliated MAX according to claim 1, characterized in that the concentration of the MAX precursor in the organic solvent is 4 mg / ml to 6 mg / ml. Claim 9 delete Claim 10 delete Claim 11 delete Claim 12 delete Claim 13 delete Claim 14 delete Claim 15 Exfoliated MAX. manufactured by a method according to any one of claims 1 to 8, characterized by having a peak at a diffraction angle 2θ = 52.0°±1.0° as a result of X-ray Diffraction (XRD) spectrum measurement, and not having peaks at diffraction angles 2θ = 9.5°±1.0°, 2θ = 19.0°±1.0°, and 2θ = 38.5°±1.0°. Claim 16 In paragraph 15, the exfoliated MAX △C (at%), defined by the following formula, has a value of 0.5 at% or more, wherein △C (at%) = C0 - C1 (where C0 is the Ti-Al atomic content (at%) of the MAX precursor measured by X-ray photoelectron spectroscopy (XPS), and C1 is the Ti-Al atomic content (at%) of the MAX layer measured by XPS after the supercritical carbon dioxide exfoliation process). Claim 17 delete Claim 18 delete Claim 19 In claim 15, the exfoliated MAX having an electrical conductivity of 250 S / cm or more at a pressure of 10 MPa.
Citation Information
Patent Citations
N-TiO2 / Ti3C2Tx heterogeneous MXene structural material as well as preparation and application thereof
CN114039060A
High-activity MXeneCF composite electrode material and application thereof in vanadium battery
CN114497591A
Skin-core MXene fiber aerogel and preparation method thereof
CN115094621A